Engaging Patients in the Use of Real-Time Electronic Clinical Data to Improve the Safety and Reliability of Their Own Care. Issue 2 (31st March 2022) - Schnock, Kumiko; Roulier, Stephanie; Butler, Jorie; Dykes, Patricia; Fiskio, Julie; Gibson, Bryan; Lipsitz, Stuart; Miller, Susanne; Shaykevich, Shimon; Bates, David; Classen, David
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: There is considerable evidence that providing patients with access to their health information is beneficial, but there is limited evidence regarding the effect of providing real-time patient safety–related information on health outcomes. The aim of this study was to evaluate the association between use of an electronic patient safety dashboard (Safety Advisor) and health outcomes. Methods: The Safety Advisor was implemented in 6 adult medicine units at one hospital in the United States. Study participants were asked to use the Safety Advisor, which provides real-time patient safety–related information through a Web-based portal. The primary outcome was the association between the application usage and health outcomes (readmission rate and mortality rate) per 3 different usage groups, and the secondary outcome was the association of Patient Activation Measure (PAM) scores with use. Results: One hundred eighty-one participants were included for the data analysis. Approximately 90% of users accessed the application during the first 4 days of enrollment: 51.6% of users only accessed it on 1 day, whereas 5.8% used it more than 3 days. Patients who used the application more had lower 30-day readmission rates ( P = 0.01) compared with the lower-usage group. The PAM scores for users of Safety Advisor (71.8) were higher than the nonpatient portal users (60.8, P < 0.0001). Conclusions: We found an association between the use of Safety Advisor and health outcomes. Differences in PAM scores between groups were statistically significant. A larger-scale randomized control trial is warranted to evaluate the impact on patient outcomes among a high-risk patient population.